Wages, Unemployment, and the Underground Economy - Ann-Sofie Kolm; Birthe Larsen (Uppsala University, Department of Economics, 2001)
While examining the macroeconomic effects of increased government control of the informal sector, this paper develops a two-sector general equilibrium model featuring matching frictions and worker-firm wage bargaining. Different goods are produced in the formal sector and the informal sector, and workers search for jobs in both sectors. We analyse the impact of higher punishment rates and a higher audit rate on labor market performance, and we find that a higher punishment rate (i) reduces the size of the informal sector and increases the size of the formal sector, (ii) decreases real producer wages in both sectors, and (iii) reduces the unemployment rate. The effect of a higher audit rate is less clear. We find that a higher audit rate (i) reduces the size of the informal sector relative to the size of the formal sector, and (ii) has an ambiguous impact on unemployment and real wages.
Keywords: H26; 330; Tax evasion; underground economy; matching; bargaining; unemployment; Schattenwirtschaft; Arbeitsangebot; Kontrolle; Mehr-Sektoren-Modell; Allgemeines Gleichgewicht; Theorie